Image rejection mixer based on a bidirectional phase modulator with full-spectrum utilization. Issue 2 (19th January 2020) - Chen, Dan; Shang, Tao; Li, Gufeng; Liu, Xiongchao; Zhang, Yinling
ABSTRACT: An all-optical image rejection (IR) mixer, based on a dual electrical port phase modulation (PM) in a Sagnac loop and a wavelength division multiplexer (WDM), is proposed. The radio frequency (RF) and the local oscillator signals are loaded onto the two electrical ports of the PM, respectively. The two down-conversion channels are obtained with the use of WDM. A pair of phase orthogonal down-converted intermediate frequency (IF) signals are obtained by properly adjusting polarization controller. Then an electrical low-frequency 90 ∘ hybrid coupler (90 ∘ HC) combines the two IF signals to double the desired IF signal and suppress the image interference IF signal. In the simulation, a 30-GHz RF signal is successfully down-converted to 1 GHz with about 57 dB IR. Compared with the IR mixer based on two parallel PMs, conversion efficiency is improved about 6 dB.